GENOTYPING OF HOLSTEIN FRIESIAN CROSSBRED CATTLE FOR BOVINE CITRULLINEMIA BY PCR-RFLP - Chavan; Pawar; Khade; Sawane; Komatwar; Chopade (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was undertaken in 30 HF and HF crossbred cattle from the Holstein Friesian crossbreds of Nalawade cattle farm, Ambarnath and from Manchar village in Pune district with the objective to find out genotype for Bovine citrullinemia using PCRRFLP. Citrullinemia is a rare inherited disorder caused by a deficiency or lack of the enzyme arginosuccinate synthetase (ASS) which plays important role in urea cycle, lack of this enzyme results in hyperammonemia. For this study, the isolation of DNA was done by phenol: chloroform method. The polymerase chain reaction (PCR) amplification of ASS gene was carried out which showed 185-bp DNA fragment. The PCR products were digested overnight by using Ava II restriction enzyme and it yielded two bands of 103 and 82bp respectively, for normal animals. None of the animals showed three bands of 185, 103 and 82bp, as reported in Bovine citrullinemia carriers, indicating all the HF and HF crossbred cattle were homozygous dominant genotype for ASS gene.